RppM, Encoding a Typical CC-NBS-LRR Protein, Confers Resistance to Southern Corn Rust in Maize - Wang, Shuai; Wang, Xiaqing; Zhang, Ruyang; Liu, Qian; Sun, Xuan; Wang, Jidong; Wang, Yuandong; Xing, Jinfeng; Liu, Ya; Zhao, Yanxin; Shi, Zi; Su, Aiguo; et al. (Frontiers in Plant Science, 2022)
Southern corn rust (SCR) caused by Puccinia polysora Underw. poses a major threat to maize production worldwide. The utilization of host SCR-resistance genes and the cultivation of resistant cultivars are the most effective, economical strategies for controlling SCR. Here, we identified and cloned a new SCR resistance gene, RppM, from the elite maize inbred line Jing2416K. RppM was found to encode a typical CC-NBS-LRR protein localized in both the nucleus and cytoplasm. This gene was constitutively expressed in all tissues and at all examined developmental stages, with the strongest expression detected in leaves at the mature stage. A transcriptome analysis provided further evidence that multiple defense systems were initiated in Jing2416K, including pathogen-associated molecular pattern-triggered immunity and effector-triggered immunity, reinforcement of cell walls, accumulation of antimicrobial compounds, and activation of phytohormone signaling pathways. This result suggests that RppM activates other defense pathways while recognizing avirulence effectors, thereby facilitating the complete resistance of Jing2416K to the SCR pathogen. Finally, we developed functional Kompetitive allele-specific PCR markers for RppM using two conserved SNP sites and successfully applied these functional markers for the detection of RppM and the cultivation of resistant maize cultivars, demonstrating their great potential utility in maize breeding.